Hidden divide in literacy gap of muslim women from online gender based violence - Anggreni, Likha Sari; Virga, Rika Lusri; Aprianto, Yudie; Idowu, Olumayowa Adeleke (Universitas Padjadjaran, 2026)
Background: In the growth of the digital environment, women face structural vulnerabilities, especially in cases of Online Gender-Based Violence (OGBV) in Indonesia. Purpose: Many studies expose how skilled digital and technological mastery among top activists, but a significant gap remains in understanding how the digital divide impacts grassroots Muslim women’s safety. This research seeks to chart the digital gap among members of Nasyiatul ‘Aisyiyah in Yogyakarta and Fatayat NU in Kediri, to see how the gap affects OGBV prevention. Methods: The study adopted a qualitative semi-ethnographic approach, including in-depth interviews, field observations, and document analysis. The study adopted a qualitative semi-ethnographic approach involving in-depth interviews with three members of Aisyiah and Fatayat in Yogyakarta and Kediri. Data were also supplemented by observing their daily activities while accessing digital media and documenting their past activities. Results: The results revealed a hidden divide among less critical women in digital literacy and particularly technical security, as well as formal reporting systems, despite access through their devices. In addition, the culture within that society has influenced how women perceive and address online threats. Conclusion: The findings indicate that the digital divide is a structural problem and that it contributes to women’s ability to digitally defend themselves in times of crisis. Implications: In intellectual terms, these findings depict a complex picture of the tiptoeing line that lies in Islamic gender and communication discourses. In reality, the research implies that community-based literacy initiatives should consider integrating digital safety with religious morals. It also highlights the immediate imperative of multi-stakeholder cooperation among religious communities, state actors, and digital platforms to redress the silencing of women.